OS CRIMES DE COLARINHO BRANCO: UMA ANÁLISE ACERCA DA IMPUNIDADE PENAL NO SISTEMA BRASILEIRO - EMANUELLA DE SOUZA REIS (2023)
This article focuses on examining criminal impunity in white-collar crimes in Brazil. These crimes involve privileged individuals who abuse their professional positions to commit offenses such as corruption and money laundering. Law No. 7,492/86 aims to punish these prominent criminals. However, impunity occurs due to both the selectivity of the judicial system, often influenced by inequality in society, allowing those with greater economic power to escape legal consequences, while authorities tend to treat them differently. Additionally, the lack of transparency in the media contributes to concealing or minimizing the criminal actions of these individuals, making it difficult for public awareness and pressure for accountability. To achieve this, the article was based on both a qualitative and quantitative methodology, which illustrated the impunity of these crimes in the country.